(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
From time to time, companies need to reconsider the management of their various marketing channels through monitoring, review, and development, especially in light of successive crises, including the total and partial closure of markets as happened during the COVID-19 pandemic. Companies also need to keep up with developments in modernizing their distribution activities and seeking competitive distribution outlets in order to maintain their position in their current market, or expand their marketing and distribution activities to increase their market share, thus achieving the goal of reaching the largest possible number of customers, based on the premise that there is a relationship between managing distribution channels and improving communication with customers, as customers today are a fundamental basis for enhancing the growth of companies’ economies by meeting their needs and desires and communicating with them continuously. As well as diagnosing the reality of the research variables in the researched company, and showing the strength of the relationship and impact between the main variables, and the research community was represented by the employees of Al-Basha Company for Soft Drinks / Nineveh, as well as the agents dealing with it, and the sample consisted of (70) people who have knowledge in the marketing field. It was used for statistical methods of simple linear correlation and simple linear regression coefficient, in addition to using (t) test to test the significance of the simple correlation coefficient, and (f) test to test the significance of the linear regression coefficient. The research reached a number of conclusions, the most important of which were: The management of marketing channels works to improve communication with end customers in particular, and the intermediaries and agents spread in the market across its multiple branches in general. E-marketing in light of the current technical developments, especially that the sale of products is now through websites and social media platforms, as well as activating the free delivery service provided by retail stores to end customers.